Earthquake resistance of buildings on thawing permafrost grounds - T.A. Belash (Инженерно-строительный журнал, 2020)
A feature of the structural solution of the building is the presence of a solid underground foundation in the form of a three-dimensional rigid reinforced concrete platform. The building will be erected on thawing grounds; thawing takes place during the entire period of operation. Theoretical analysis of stress-strained building structures exposed to static and seismic loads has been carried out. Seismic load was determined by a specified response spectrum method. The calculation was carried out taking into account the presence of a thawing basin under the foundation with the size of the bowl varying from 6 m to 27 m. It was found that the building structures exposed to a seismic load are subject to increased stress and strain as compared with the static load exposure. Evaluation of the obtained values has shown that they did not exceed the permissible limits for the accepted strength properties of structural materials even in conditions of a maximum thawing basin. Foundation settlement is gradual. The adopted foundation structure design ensures the required earthquake resistance of the building in the given construction conditions.